Promotion of Improved Onion (Nafis Variety) Production Technology under Irrigated Conditions in Nyangatom District, Low Land Area of South Omo Zone - Tadesse, Awoke; Adicha, Asmera; Eshibel, Atlaw; Geberemeskel, Yibrah; Tadesse, Anteneh (Research on World Agricultural Economy, 2023)
Onion is an important cash crop that could enhance the income of agro-pastoralists in Nyangatom woreda as the area has huge potential for water availability from the Omo River and fertile land. However, access to improved onion variety is limited in the area. Thus, this study aimed to demonstrate the improved onion variety with its agronomic management in the production season. Onion growers were purposely selected and have taken training on onion production by using recommended doses of fertilizers, pesticides, irrigation, and suitable agronomic practices. Each agro-pastoralist covered 0.064 hectares of land by improved onion. The recorded data from the field experiment and agro-pastoral perceptions were analyzed through simple descriptive and preference ranking tools. From the result of the demonstration trial, the mean bulb yield of the improved onion (Nafis variety) was 125 qt/ha. The average return obtained from the sale of onion bulbs per hectare was 334,925 Ethiopian birr. Moreover, the benefit-to-cost ratio of improved onion production was 8.34:1, which indicates the benefits outweigh the costs, suggesting a positive return on improved onion production in the area. The agro-pastoralist’s preference further showed that the Nafis variety was the best one or superior to the local variety in terms of its high-yielding ability, dark green leaf color, medium bulb size, and market preference. Therefore, the authors suggest the respective government and non-government bodies to further promote improved onion in the area.